Testing an EU-Candidate's Place on the Maps of Global Economic, Political and Social Values: The Case of Turkey - Arno Tausch; Almas Heshmati (Institute for the Study of Labor (IZA), 2014)
Following the attempt by Alesina and Guiliano (2013) to measure global culture and to project these measurements onto real choropleth geographical world maps, we utilize the data from the World Values Survey (WVS) to arrive at robust measurement scales of global economic, political and social values and to assess Turkey's place on them. Our study, which is based on 92,289 representative individuals with complete data in 68 countries, representing 56.89% of the global population, looks at hard-core economic values in the countries. From our new nine dimensions for the determination of the geography of human values, based on a promax factor analysis of the available data, we use six factor analytical scores to calculate a new Global Value Development Index, which combines: avoiding economic permissiveness; avoiding racism; avoiding distrust of the army and the press; avoiding the authoritarian character; tolerance and respect; and avoiding the rejection of the market economy and democracy. Our results show that the five best ranked countries are all western democracies. Our global value development index ranks Morocco twelfth - just behind the USA. Turkey is ranked 25, ahead of several EU member countries. But there are still considerable deficits concerning the liberal values components, which are very important for effective democracy, and there are very large regional differences, confirming the dictum by Huntington (1996) about Turkey as a torn country. The deficits suggest that the Turkish state, Turkish civil society and European decision makers would be well advised to continue to support civil society and secular democracy in Turkey.
Keywords: C43; F50; Z12; D73; 330; index numbers and aggregation; international relations; international political economy; religion; bureaucracy; administrative processes; corruption